Discovery of Inhibitors of DNA Methyltransferase 2, an Epitranscriptomic Modulator and Potential Target for Cancer Treatment - Schwickert, Marvin; Fischer, Tim R.; Zimmermann, Robert A.; Hoba, Sabrina N.; Meidner, J. Laurenz; Weber, Marlies; Weber, Moritz; Stark, Martin M.; Koch, Jonas; Jung, Nathalie; Kersten, Christian; Windbergs, Maike; et al. (Journal of medicinal chemistry, 2022)
Selective manipulation of the epitranscriptome could be beneficial for the treatment of cancer and also broaden the understanding of epigenetic inheritance. Inhibitors of the tRNA methyltransferase DNMT2, the enzyme catalyzing the S-adenosylmethionine-dependent methylation of cytidine 38 to 5-methylcytidine, were designed, synthesized, and analyzed for their enzymebinding and -inhibiting properties. For rapid screening of potential DNMT2 binders, a microscale thermophoresis assay was established. Besides the natural inhibitors S-adenosyl-L-homocysteine (SAH) and sinefungin (SFG), we identified new synthetic inhibitors based on the structure of N-adenosyl-2, 4-diaminobutyric acid (Dab). Structure-activity relationship studies revealed the amino acid side chain and a Y-shaped substitution pattern at the 4-position of Dab as crucial for DNMT2 inhibition. The most potent inhibitors are alkyne-substituted derivatives, exhibiting similar binding and inhibitory potencies as the natural compounds SAH and SFG. CaCo-2 assays revealed that poor membrane permeabilities of the acids and rapid hydrolysis of an ethylester prodrug might be the reasons for the insufficient activity in cellulo.